Interrelated Channel Current and Oxide Leakage Current Density in a MOSFET Device - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2024)
This research paper discusses the observed lower Fowler-Nordheim (FN) onset electric field in the thermal SiO2 grown on the (110) surface of the 4H-SiC semiconductor than on the (0001) oriented surface. This forms the metal-oxide-semiconductor (MOS) device which is the essential part of the MOSFET device as a transistor. First, the FN onset field is revised to a new value of 4.6 MV/cm, and then the mechanism for the lowering of the field is described.